Thermo-viscoplastic constitutive modeling of semicrystalline polymers with a novel perturbation-based return-mapping algorithm - Vadizadeh, Rahele; Zajkani, Asghar; Mirkhalaf, Mohsen (International journal of non-linear mechanics, 2026)
The elasto-viscoplastic behavior of semicrystalline polymers is modeled using an implicit finite element framework across three distinct temperature regimes: below, near, and above the glass transition temperature. The study considers varying strain rates under both isothermal and adiabatic conditions. A phenomenological DSGZ (Duan, Saigal, Greif, and Zimmerman) viscoplastic model is developed specifically for semi-crystalline thermoplastics with high thermal and mechanical resistances. To address the challenges of highly nonlinear terms, a novel perturbation-based return-mapping approach is introduced, ensuring stable and efficient stress integration. Additionally, an optimized procedure is seamlessly integrated to facilitate material parameter identification essential for the viscoplasticity model. Simulation results exhibit strong agreement with a wide range of experimental data, highlighting the necessity of temperature-specific parameter sets. Furthermore, a sensitivity analysis is conducted to assess the influence of key parameters on mechanical response. These findings establish a robust computational framework for accurately simulating and designing thermoplastic components subjected to complex thermo-mechanical loading scenarios. •Finite element modeling of viscoplastic responses of semicrystalline polymers is considered.•Novel perturbation return mapping algorithm is introduced for implicit constitutive equations.•Consistent DSGZ model parameters related to quasi-static and dynamic strain rates are obtained.•Efficient parameter identification using an optimization scheme improves simulation results.•Distinct parameter sets identified for different temperature regimes at various strain rates.